Subarachnoid hemorrhage rebleeding in the first 24 h is associated with external ventricular drain placement and higher grade on presentation: Cohort study. (November 2020) - Lu, Victor M.; Graffeo, Christopher S.; Perry, Avital; Carlstrom, Lucas P; Casabella, Amanda M.; Wijdicks, Eelco F.M.; Lanzino, Giuseppe; Rabinstein, Alejandro A.
Highlights: Early rebleeding in first 24 h after aneurysmal subarachnoid hemorrhage (SAH) is poorly defined. Extraventricular drain and higher SAH grade are significant predictors of early rebleeding . Higher SAH grade prior to rebleeding is associated with unfavorable functional outcome. Anticoagulation, aneursym size and location were not associated with early rebleeding . Abstract: Background: Rebleeding after aneurysmal subarachnoid hemorrhage (aSAH) confers a poor prognosis; however, risk factors and differential outcomes associated with early rebleeding in the first 24 h after symptom presentation are incompletely understood. Methods: A retrospective cohort study of all aSAH presenting to our institution between 2001 and 2016 was performed. Early rebleeding events were defined as clinical neurologic decline with radiographically confirmed acute intracranial hemorrhage within 24 h after symptom presentation. Univariate and multivariate logistic regression analyses were used to assess clinical associations, with a specific focus on baseline Glasgow Coma Score (GCS), World Federation of Neurosurgical Societies (WFNS), and modified Fisher scores. Results: Of 471 aSAH cases, 33 (7%) experienced early rebleeding . Multivariate regression identified extraventricular drain (EVD) placement (OR = 2.16, P = 0.04) and WFNS 3–5 (OR = 2.69, P = 0.02) as significant predictors of early rebleeding . Good functional outcomes were observed in 8 patients with early rebleeding (24%), all of whom underwent aneurysm treatment. Higher SAH grade prior to rebleeding (WFNS 3–5) was significantly associated with increased odds of an unfavorable functional outcome (OR = 8.09, P < 0.01). Anticoagulation, aneurysm size and location were not significantly associated with either early rebleeding incidence or functional outcome. Conclusions: Early rebleeding in aSAH is associated with unfavorable functional outcomes. EVD placement and higher SAH grade on presentation appear to be significantly and independently associated with increased risk of rebleeding within first 24 h, as well as unfavorable long-term functional outcome; however, the clinical benefit of hyper-acute aneurysm treatment requires further investigation.